The Relationship between AI Chatbot Attributes and Customer Experience in the E-Commerce Industry among Gen Y in Selangor - Chang, Xin Qiau; Kamaruddin, Nor Kamariah (Research in Management of Technology and Business, 2026)
The increasing number of e-consumers and rapid changes in business dynamics have highlighted the importance of delivering a superior customer experience in e-commerce. The industry has seen remarkable growth recently, fueled by digital adoption, technological progress, and evolving customer expectations. This shift has also transformed the design and function of artificial intelligence (AI) within the e-commerce industry. One of the innovations in this industry is the AI chatbot, which is an essential tool for improving customer service and enhancing communication. The purpose of this research was to examine the relationship between AI chatbot attributes and customer experience in the e-commerce industry among Gen Y in Selangor. The study focuses on a population of 2,118,153 Gen Y from Selangor. To ensure a representative sample, the researcher employed the Krejcie and Morgan table, a representative sample size of 384 was selected. The research employed a quantitative approach, collect data by using an online survey through Google Forms. The data was analyzed using Statistical Package for the Social Sciences (SPSS). The findings showed that usability and responsiveness have a positive and significant relationship with customer experience. Based on the findings, practical recommendations are provided for businesses to effectively utilize AI chatbots to boost customer satisfaction.